2023
DOI: 10.3390/agronomy13030811
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Global Faba Bean Germplasm Resources Based on the 130K TNGS Genotyping Platform

Abstract: Novel germplasm resources are the key to crop breeding, with their genetic diversity and population structure analysis being highly significant for future faba bean breeding. We genotyped 410 global faba bean accessions using the 130K targeted next-generation sequencing (TNGS) genotyping platform, resulting in a total of 38,111 high-quality SNP loci by high-standard filtering. We found the polymorphism information content (PIC) and Nei’s gene diversity were 0.0905–0.3750 and 0.0950–0.5000, with averages of 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
3
4
1
Order By: Relevance
“…LD values dropped from 0.140 to 0.125, with the increase of physical distance from 126.6 kbp to 151.8 kbp. Low LD in faba bean was previously reported ( Skovbjerg et al., 2023 ; Zhang et al., 2023 ) when comparing different faba bean diversity panels. Thus, the EUCLEG collection was the one showing lower LD blocks (higher recombination), an expected outcome in outbreeding species with high genetic diversity ( Pégard et al., 2023 ; Skovbjerg et al., 2023 ; Zanotto et al., 2023 ; Zhang et al., 2023 ).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…LD values dropped from 0.140 to 0.125, with the increase of physical distance from 126.6 kbp to 151.8 kbp. Low LD in faba bean was previously reported ( Skovbjerg et al., 2023 ; Zhang et al., 2023 ) when comparing different faba bean diversity panels. Thus, the EUCLEG collection was the one showing lower LD blocks (higher recombination), an expected outcome in outbreeding species with high genetic diversity ( Pégard et al., 2023 ; Skovbjerg et al., 2023 ; Zanotto et al., 2023 ; Zhang et al., 2023 ).…”
Section: Discussionsupporting
confidence: 56%
“…Low LD in faba bean was previously reported ( Skovbjerg et al., 2023 ; Zhang et al., 2023 ) when comparing different faba bean diversity panels. Thus, the EUCLEG collection was the one showing lower LD blocks (higher recombination), an expected outcome in outbreeding species with high genetic diversity ( Pégard et al., 2023 ; Skovbjerg et al., 2023 ; Zanotto et al., 2023 ; Zhang et al., 2023 ). The rapid LD decay observed in this study (within roughly 150 kbp) revealed the variation present in a highly allogamous panmictic population and suggested that the MTAs identified (or the closely linked genes on either flanking side of the significant SNPs) were nearly or completely independent from each other and, hence, were sufficient for association mapping in faba bean.…”
Section: Discussionsupporting
confidence: 56%
“…The breeding of climate-resilient varieties requires novel traits like tolerance towards potential new insect pests, diseases, extreme heat, extreme cold, and various air/soil-pollutants. For everchanging breeding goals, different genes need to be reserved in cultivated and cultivable crop species in the form of germ plasma resources (Zhang et al, 2023). The presence of genetic diversity within and between crop plant species helps the breeders to select superior genotypes either to be directly used as new varieties or to be used as parents in the hybridization programs.…”
Section: Introductionmentioning
confidence: 99%
“…It also facilitates the development of new lines. Diversity is also important for the adaptability of crop plants to varied environments with special reference to changing climatic conditions (Zhang et al, 2023). High temperatures at the pod development stage, significantly affect the grain yield, floral development, and anthesis leading to yield losses in faba bean (Bishop et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The accurate identification of genotypes and comprehensive evaluation of genetic diversity and population structure of germplasm resources are crucial to breeding programs in terms of the proper selection of parent combinations and optimal exploitation of genetic resources [12][13][14][15]. Molecular genetic marker technology provides the most direct means of genetic relationship analysis [16].…”
Section: Introductionmentioning
confidence: 99%